Effect of banana leaf pruning on banana and bean yield in an intercropping system in Eastern Democratic Republic of Congo - Ntamwira, J.; Pypers, Pieter; Asten, Piet J.A. van; Vanlauwe, Bernard; Ruhigwa, B.A.; Lepoint, P.C.E.; Blomme, Guy (2012)
Banana-bean intercropping systems are used by many small-scale farmers in eastern Democratic Republic of Congo to maximize land use and intensify crop production. A study was conducted at the INERA Mulungu research station to determine the effect of banana leaf pruning on banana (Musa spp.) and bean (Phaseolus vulgaris, Fabaceae) yield. The East African highland cooking banana ‘Barhabesha’ was established in April 2007 at a spacing of 2 by 3 meters. The treatments consisted of different levels of banana leaf canopy coverage (5 leaves [5L] and all leaves [ALL]) and leguminous crop varieties (the bush bean ‘Ngwaku Ngwaku’ and the climbing bean ‘AND10’) which were planted in the banana plot. Bean yields were assessed during 4 cropping seasons (2008B, 2009A, 2009B and 2010A). Banana leaf pruning did not have a significant effect on time from planting to bunch harvest in either legume intercropping treatment. Banana leaf pruning did not have a significant effect on banana yield (32.3 and 28.6 t/ha for ALL; 32.2 and 26.3 t/ha for 5L for climbing and bush bean intercropping respectively). The average banana bunch weight was higher in the climbing bean (ALL: 19.4 / 5L: 19.4 kg) than in the bush bean intercropped plots (ALL: 17.2 / 5L: 16.1 kg). A reduction in the number of banana leaves (i.e. from all leaves to 5 leaves) enhanced bean yield for both legume types. Under the all leaves treatment, climbing bean yield (358 kg/ha) was slightly but not significantly higher than bush bean yield (335 kg/ha). However, it was significantly higher for the 5L treatment (512 kg/ha against 362 kg/ha). Results from a gross margin analysis of banana-bean intercropping and cropping season effects are also presented.